Character Formation Through Exemplary Methods According to Abdullah Nashih Ulwan - Muhammad Gafarurrozi (Murabby: Jurnal Pendidikan Islam, 2026)
This study aims to examine the concept and application of the role-modeling method in character development according to the ideas of Abdullah Nashih Ulwan through field research. The primary focus of the study is to understand how the values of role modeling proposed by Ulwan are applied in character education practices, particularly in the context of Islamic education within school and family settings. This study employs a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation of teachers, students, and parents at Islamic educational institutions that implement character education based on the exemplary method. Data analysis was conducted through data reduction, data presentation, and the drawing of conclusions using a descriptive-analytical approach. The research results indicate that the role modeling method is the most effective approach in shaping students’ character because it emphasizes the internalization of values through concrete behaviors demonstrated by educators, parents, and the social environment. In practice, exemplary behavior is evident through the cultivation of attitudes such as discipline, honesty, responsibility, good manners, and the performance of religious duties, all of which are directly modeled by teachers and parents. According to Abdullah Nashih Ulwan, exemplary behavior encompasses exemplary conduct in faith, worship, ethics, and social interactions, all of which form the foundation for the development of a complete Islamic personality. This study also confirms that the success of character education depends heavily on the integrity, consistency, and quality of the example set by educators in their daily lives. Thus, the concept of exemplary behavior, as defined by Abdullah Nashih Ulwan, is highly relevant to efforts to revitalize character education in the modern era, which is rife with moral and values crises.